A multiplex targeted NGS panel for identifying pathogens in canine neurological and reproductive diseases - Kattoor, Jobin Jose; Anis, Eman; Elshafie, Nelly O.; Wilkes, Rebecca P. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMultiple pathogens can infect the canine reproductive and central nervous systems, including organisms that are zoonotic, such as Brucella canis, pathogenic Leptospira spp., Anaplasma phagocytophilum, Histoplasma capsulatum, and Blastomyces dermatitidis. In this study, we developed a targeted next-generation sequencing (tNGS) panel to identify common infectious agents related to neurologic and reproductive disease in canines while incorporating less common zoonotic agents into a single test.MethodsPrimer pools were developed to detect 34 pathogens and used in two multiplex PCR assays, which were combined prior to library preparation and sequencing using Ion Torrent technology. A feasibility study was performed with known positive clinical samples, bacterial isolates, or synthetic DNA (gBlocks) spiked into nucleic acids from negative canine clinical samples.ResultsOf the 34 organisms included in the panel, 33 were detectable. Some primer sets were not specific for the intended target organism, based on BLAST analysis (NCBI) of the obtained sequences. Compared to real-time PCR assays, pathogens could be detected at Ct values from 33-38, depending on the pathogen, and at approximately 100–1000 copies based on gBlock testing. A total of 76 samples (39 positive and 40 negative) were tested, representing neurological and reproductive samples. Diagnostic sensitivity and specificity for the assay were calculated as 89% and 98%, respectively. The tNGS assay had the added benefit of strain-typing Canine distemper virus and Canine parvovirus-2 in the positive samples. For reproducibility, a blinded panel was tested by our laboratory and another laboratory using the same tNGS protocol where the assay had an agreement for 16 out of 18 samples with a Cohen’s kappa value of 0.77, indicating high reproducibility.DiscussionThe tNGS assay was not as sensitive as real-time PCR assays, which is a known limitation of this method, and was evident based on the diagnostic sensitivity testing. However, the comprehensive nature of this assay is beneficial for syndromic testing.